Spaniards, you Already Have a Heritage.The Bicentenary of the Cádiz Constitution - Zapatero Gómez, Virgilio (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
The Constitutions of 1812 and 1978 give differential treatment to some of the crucial problems of Spain’s History – such as the relationship between Church and State and the extent to which power is decentralized. Beyond this, however, there is a point of convergence, as both Constitutions also represent the two most serious attempts in Spain’s history to build a civic identity, one which could and should give rise to constitutional patriotism, regardless of any personal loyalties to ideologies, territories or classes. Both attempted to instil amongst the Spanish of their time the pride of belonging – extending beyond that of a territory or ideological community– to a society in which the values of “freedom, equality, justice, and politic pluralism” are respected, and protected. That is both the wording and the intention of our current Constitution. It was also what was attempted, in its own way, in Spain in 1812.
Keywords: Civic identity; patriotism; Constitution; Cosnstitution 1812; Constitution 1978